Assessment and validation of ICP-MS and IC-ICP-MS methods for the determination of total, extracted and speciated arsenic. Application to samples from a soil-rice system at varying the irrigation method. (15th January 2022) - Langasco, Ilaria; Barracu, Francesco; Deroma, Mario Antonello; López-Sánchez, José Fermín; Mara, Andrea; Meloni, Paola; Pilo, Maria Itria; Estrugo, Àngels Sahuquillo; Sanna, Gavino; Spano, Nadia; Spanu, Antonino
Abstract: Food is the major route of arsenic (As) intake for humans, and rice is the staple food for more than half of the world's population. Unfortunately, rice bioaccumulates large amounts of As from the paddy field, and the toxicity of this element in the kernel is closely linked to its chemical form. Therefore, it is of the utmost importance to have access to an integrated set of analytical methods, capable of measuring the concentration of As in its various chemical forms in soil and rice. Hence, the principal aim of this study was to assess and validate a group of inductively coupled plasma – mass spectrometry (ICP-MS) and IC-ICP-MS (IC, Ionic Chromatography) methods designed to measure the amount of the total or extracted As and its main chemical species (As(III), As(V), monomethylarsonic acid, MMA, and dimethylarsinic acid, DMA) in flours of rice grain and in soils. Great attention has been given to the assessment and the optimization of extraction methods of As species from these matrices. No appreciable interconversion among As species has been observed using an aqueous solution 1 mol dm −3 of phosphoric acid and 0.5 mol dm −3 of L (+)-ascorbic acid for the extraction from soils, and an aqueous solution 0.2% (w/v) of nitric acid for the extraction from rice flour. Validation has been successfully accomplished in terms of limit of detection, limit of quantification, linearity and accuracy. In addition to many certified reference materials, these methods have been tested on real samples of soils and rice grains of the Aleramo genotype obtained through traditional or intermittent irrigation methods. Data obtained revealed the critical role of the intermittent irrigation methods in determining the nature and the amount of the As chemical species in rice grains as well as in soils. As(V) is the only species found in soil irrigated by sprinkling, while the most toxic As(III) dominates in soil irrigated by continuous flooding. On the other hand, the most abundant species found in continuously flooded Aleramo rice grains are As(III) and – mostly – DMA, whereas As(V), less toxic than As(III), represents 60% of the total inorganic compounds measured in sprinkler-irrigated rice. Lastly, the total amount of As measured in this rice is 3.8% of that measured in rice irrigated by continuous flooding. Graphical abstract: Image 1 Highlights: ICP-MS based methods measured total, extracted and speciated As in soil and rice. ICP-MS and IC-ICP-MS methods are more sensitive and accurate than literature ones. Irrigation methods affect equilibrium of As chemical species in soil-rice systems.